HEAVY METAL DISTRIBUTION, BIOACCUMULATION AND HEALTH RISK ASSESSMENT OF RICE CULTIVATED IN IDAH, KOGI STATE - Owoleke, Veronica Amina; Olubiyo, Gloria Taiye; Isah, Haruna Mohammed; Owoleke, Oluwafemi Stephen; John, Ojo Isah (FUDMA Journal of Sciences, 2026)
This study evaluated the distribution, bioaccumulation, and health risks of heavy metals in soil, water, and different parts of rice plants (roots, stems, and grains) cultivated in the floodplain of River Niger in Idah, Kogi State. Soil, water, and plant samples were collected and analyzed for arsenic (As), cadmium (Cd), lead (Pb), zinc (Zn), chromium (Cr), and nickel (Ni) using standard analytical procedures. Soil physicochemical properties were also determined, and statistical and risk assessment models were applied. Results showed that mean metal concentrations in soil followed the order Cr (22.7 mg/kg) > Pb (18.3 mg/kg) > Cd (0.83 mg/kg), indicating moderate contamination. Water samples contained lower concentrations, while rice grains accumulated detectable levels of Pb (4.45 mg/kg) and Cd (0.35 mg/kg). Significant variation (p < 0.05) in metal distribution across plant parts was observed, with accumulation highest in roots and lowest in grains. Bioaccumulation analysis revealed Cd as a strong accumulator (BAF = 1.08), while translocation factors indicated moderate movement of metals within the plant system. Health risk assessment indicated that individual Target Hazard Quotients were below 1; however, the cumulative Hazard Index exceeded unity, suggesting potential health risks from combined exposure. Cancer risk values for Cd and As (~10⁻³) exceeded acceptable limits. The findings highlight the need for continuous monitoring and improved agricultural practices to minimize heavy metal contamination and ensure food safety.
Keywords: Food safety; Target Hazard Quotient; Heavy metal; Rice; Metal uptake